Updates in Multiple Sclerosis Imaging - Schmidt, Tyler M.; Abdel-Wahed, Lama (Seminars in Neurology, 2025)
Magnetic resonance imaging (MRI) remains an integral diagnostic tool in multiple sclerosis (MS), for both making the initial diagnosis and monitoring for disease relapse and progression. Despite the applied use of MRI according to the revised McDonald's criteria in 2017, there has been persistent low diagnostic specificity, especially as it pertains to differentiating radiologically isolated syndrome from alternative diagnoses that mimic demyelination. This report will provide an overview of recent paraclinical innovations, with a focus on MRI biomarkers and parameters such as the central vein and paramagnetic rim signs. Utilizing these tools in clinical practice will hopefully improve precision in the diagnosis and monitoring of MS and reduce the risk of false-positive diagnoses.
Keywords: multiple sclerosis; magnetic resonance imaging; central vein; paramagnetic rim